Introduction to Laws of Social Reproduction Lectures - Kotiswaran, Prabha (feminists@law, 2023)
Prabha Kotiswaran introduces the following three lectures by Kerry Rittich (2020), Silvia Federici (2021) and Veronica Gago (2022), which emanated from an EU-supported research project titled 'Laws of Social Reproduction'.